Perancangan Sistem Informasi Akuntansi Biaya Berbasis Pesanan Menggunakan Microsoft Visual Studio 2017 - Dwiputri, Ai Elpa; Rosmiati, Mia (Labkat Press KA FTIK UNIKOM, 2023)
The Accounting Information System (AIS) is crucial for a company's commercial operations to run smoothly. One type of AIS is the Cost Accounting Information System which has a vital role, especially in manufacturing companies. More specifically, AIS Cost also depends on the method of collecting costs used by a company which consists of two types, namely process-costing and job order-costing. MSMEs MMC Fashion Knitting one of the manufacturing companies in Bandung that produces based on orders (job order-costing) still uses the Cost Accounting Information System manually so that the owner does not know the exact production cost and gross profit of each order. This study aims to create a simple application to process the Accounting Information System of Job Order Costing that can help the company's operational activities. Descriptive-qualitative research methodology is being employed. Interviews and documentation in the form of primary and secondary data were used to acquire the information. The System Development Life Cycle (SDLC) approach and Microsoft Visual Studio 2017 are used in this study's application design. The results of this study are the Accounting Information System of Job Order Costing Application which can produce output including sales order letter, production order letter, bill of material, production activities list, material stock report, cost of goods manufactured report, and income statement with variable costing method.